A comprehensive insight into the effects of acidification on varied-sized pores in different rank coals - Jiang, Peiwen; Yang, Chengtao; Chen, Feng; Li, Bing; Ren, Jiangang; Liu, Jianbao; Song, Zhimin (Frontiers in Earth Science, 2023)
Elucidating the evolution law of coal pore structure under acidification is crucial for guiding the practical application of acidizing technology and improving the production of coalbed methane. To comprehensively investigate the influence of acidification on varied-sized pores in different rank coals, in this study, fat coal, meagre coal and anthracite coal were collected and acidified with a mixed solution composed of hydrochloric acid (9 wt%) and hydrofluoric acid (3 wt%). An approach integrating low-pressure CO2 adsorption (LPGA-CO2), low-temperature N2 adsorption (LTGA-N2) and Mercury intrusion porosimetry (MIP) was adopted to fully characterize the varied-sized pore structure before and after acidification to eliminate the limitations of single method. The results demonstrated that acid treatment improved the pore opening degree and connectivity in coal, but had essentially no effect on the pore shape. After acidification, all the coal samples showed significant increases in the porosity and total pore volume, which was mainly contributed by the numerous newly formed large mesopores and macropores, especially the macropores (with an average contribution rate of 74.59%). Taken as a whole, acid treatment had the largest impact on macropores, followed by mesopores, and the smallest impact on micropores. In addition, the variation trend of total specific surface area (SSA) under acidification was primarily determined by micropores. For the three different rank coals selected in this study, the total SSA of fat coal (PM) was more easily affected by acidification and had the largest percentage increase after acid treatment, followed by anthracite coal (YM), while that of meagre coal (LA) decreased slightly. This difference was driven primarily by the different variation trend of micropore SSA in different rank coals. After acidification, the SSA of ultra-micropores and super-micropores all increased in fat coal (PM) and anthracite coal (YM), whereas for meagre coal (LA), although ultra-micropores SSA increased, super-micropores SSA decreased, which ultimately led to the slight decrease of its micropore SSA. Moreover, the total pore volume increment of coal was closely related to the macropore volume increment under acidification, but not significantly related to the coal maturity,which might indicate that, compared with coal rank, the mineral content in coal might be a more important consideration when measuring the applicability of acidification technology.